Evaluating municipal incinerated bottom ash as a sand replacement in foamed mortar: Effects of air foam and silica fume modification - Trong Phuoc Huynh; Vo Thi To Trinh; Tri Ho Minh Le (CTU Journal of Innovation and Sustainable Development)
This study presents an investigation into the feasibility of utilizing municipal incinerated bottom ash (MIBA) as a substitute for sand in foamed flowable mortar, with a specific focus on its applicability as flowable fill materials. Employing a mix design strategy with a fixed cement content of 180 kg/m³, the research systematically varies air foam (AF) percentages (15-20% by volume), MIBA replacement levels (0-40%), and introduces silica fume (SF) at a fixed rate of 12% by weight of fine aggregate. The study assesses flowability, setting times, and compressive strength under diverse curing conditions, including normal and H2SO4 (3%) curing. H2SO4 was employed to simulate harsh curing conditions in an acidic environment, providing insights into the mortar's behavior under more aggressive circumstances. Remarkably, at 40% bottom ash and 20% air foam, flowability experiences a significant 29.3% reduction, reaching 163.4 mm. Setting times prolong with increasing MIBA percentages, showing a substantial 64.7% increase at 40% replacement. Silica fume demonstrates its positive impact, revealing approximately 16% enhanced compressive strength in mixtures with air foam under normal curing conditions. Under H2S04 curing, the mixture with 15% air foam and 12% silica fume experiences a slight reduction in compressive strength, showing a 13.7% decrease from 0.73 MPa under normal curing to 0.63 MPa. This research unveils the intricate interplay of variables, providing valuable insights for optimizing sustainable mortar formulations. Consequently, it contributes to environmentally conscious construction practices by bolstering the mechanical properties of the mortar.